Pendampingan Usaha Ekonomi Kerakyatan di Desa Kembang Pacitan: Pembuatan Bakso Tusuk (Ikan) - Nur Edi Prabha Susila Yahya; Rabbani Al-Lontari, M. Yazid Nur (Dharmahita: Journal of Community Service and Development, 2025)
The Economic Sector is the heart of most people's lives, especially in areas with tourism potential. This community service research aims to explore the economic potential of Kembang Village in Pacitan Regency. Considering the challenges faced by the community after the Covid-19 pandemic, a people-centered economic approach through the optimization of natural resource management based on fish, which is abundant in Pacitan Regency, is considered a solution that needs to be implemented. The research method used is qualitative. Data collection techniques include observation, in-depth interviews, and literature studies to obtain complete information on the potential of natural resources in Kembang Village. The main focus of this research is on optimizing natural resource management, which is expected to trigger economic circulation, especially in the Micro, Small, and Medium Enterprises (MSME) sector. One of the strategies proposed as a result of the research is through training and implementation of food processing technology, particularly in the context of making fish meatballs on skewers. As a form of cuisine, fish meatballs on skewers have a unique taste, aroma, and character and can be publicized through traditional culinary festivals and promoted as a specialty of the village. This is intended to improve the economy of the people of Kembang Village, Pacitan.